ادارة الازمات الاسرية وعلاقتها بإدارة الصف لدى المعلمات الامهات - إبراهيم أبو عقيل (Scientific Journal of University of Benghazi, 2020)
This research aims to investigate of home crises management and its relationship to classroom management among maternal teachers from their point of view. A sample of (125) teachers as mothers was selected using a stratified random method. A scale of home crisis management skills, and a scale for classroom management skills were used. The researchers adopted the descriptive correlational survey method to conduct this research. Results showed that the degrees of home crisis management skills and classroom management skills scored high degrees. Results also showed that there were no statistically significant differences due to the variables (number of family members, the stage the mother taught and teacher's age). Nevertheless, There were statistically significant differences due the family monthly income variable for the favor of high-income people. Moreover, results showed a positive correlation between the skills of managing home crises and classroom management skills among teacher-mothers. In the light of these results, some recommendations and suggestions were stated.